1981
DOI: 10.1073/pnas.78.6.3734
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of UV-sensitive DNA repair mutants of Chinese hamster ovary cells.

Abstract: Mutant lines of Chinese hamster ovary cells that show hypersensitivity to killing and mutagenesis by UV light were analyzed by genetic complementation analysis to determine whether defects in different gene loci might underlie a common cellular phenotype. To facilitate rapid screening of mutant clones, a procedure was devised that allowed presumptive complementation to be assessed on the basis of the frequency of UV-resistant cells after fusion by polyethylene glycol. Four classes were identified among 44 clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
67
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 15 publications
2
67
0
Order By: Relevance
“…which belongs to the second complementation group of UV-sensitive CHO mutants. This is the former first complementation group (22). At the UCLA meeting on DNA damage processing in Taos, N.M., in 1988, it was agreed that the nunibers of the first two complementation groups would be switched to allow correlation of the numbers of the cloned human DNA repair genes ERCC-1 and ERCC-2 with the numbers of their respective complementation groups (25).…”
mentioning
confidence: 99%
“…which belongs to the second complementation group of UV-sensitive CHO mutants. This is the former first complementation group (22). At the UCLA meeting on DNA damage processing in Taos, N.M., in 1988, it was agreed that the nunibers of the first two complementation groups would be switched to allow correlation of the numbers of the cloned human DNA repair genes ERCC-1 and ERCC-2 with the numbers of their respective complementation groups (25).…”
mentioning
confidence: 99%
“…Sci. USA 91 (1994) 2 series of genes that are required for the functioning of nucleotide-excision repair in mammalian cells (5,6). In a previous study, transfection of CHO UV41 cells with human DNA resulted in correction of cells to repair proficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Seven human genes in this pathway have been identified and cloned by using mutants developed in rodent cells or derived from humans having the disorder xeroderma pigmentosum (XP) (4). Studies ofhamster and mouse mutant lines first identified five genetic complementation groups (5,6) having extreme UV-radiation sensitivity and excision-repair deficiency. From these groups of mutants, the complementing human genes ERCCI (7), XPD/ERCC2 (8), XPB/ERCC3 (9), and XPG/ERCCS (10) were cloned and shown to substantially overlap (9,(11)(12)(13) with the seven excision-deficient groups of XP (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations